Assessment of Energy Efficiency and Conservation at the UNTAG Surabaya Rectorate Building Using EDGE and GREENSHIP - Kresna Gemilang; Endah Safitri; Sholihin As'ad (CV FOUNDAE, 2026)
The building subsector is the largest contributor to greenhouse gas emissions in Indonesia’s energy sector, with approximately 90% of its emissions stemming from electricity consumption. The implementation of green building concepts is one of the efforts to improve energy efficiency and reduce these emissions. This study aims to evaluate the energy efficiency and conservation (EEC) score in the GREENSHIP rating system and compare it with energy savings estimates using the excellence in design for greater efficiencies (EDGE) Building App at the Rectorate Building of the University of 17 August 1945 in Surabaya. The study employed a quantitative descriptive method based on electricity consumption data and observations of electricity usage for the GREENSHIP evaluation, as well as calculations of the Window-to-Wall Ratio (WWR) and building characteristics for energy performance simulations using the EDGE Building App. The results show that the GREENSHIP EEC score reached only 7 out of a total of 36 points, while the EDGE simulation indicated a potential energy savings of 26.37%. These results indicate that EDGE focuses on the percentage of energy savings compared to a baseline building, whereas GREENSHIP evaluates the implementation of energy management, efficiency, and conservation strategies more comprehensively. Therefore, a high level of energy savings does not necessarily result in a high GREENSHIP score without the comprehensive application of energy efficiency criteria.